1987
DOI: 10.1523/jneurosci.07-04-00943.1987
|View full text |Cite
|
Sign up to set email alerts
|

Centrifugal organization of direction preferences in the cat's lateral suprasylvian visual cortex and its relation to flow field processing

Abstract: The cerebral cortex of the cat contains between 1 and 2 dozen representations of the visual field with different functional specializations. Six visual field maps lie along both banks of the suprasylvian sulcus, lateral and anterior to the visual areas in the occipital cortex. We have studied single-unit receptive field properties and their global organization across the visual field in 2 of these lateral suprasylvian areas, PMLS (essentially the Clare-Bishop area) and PLLS. Most neurons in PMLS and PLLS displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
92
3

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(120 citation statements)
references
References 67 publications
(88 reference statements)
25
92
3
Order By: Relevance
“…The average of the oscillation frequency was 52 Hz (SD = ±12 Hz; n = 19) and thus in the same range as that of responses in area 17 (11)(12)(13). In agreement with previous reports (18)(19)(20), most of the cell clusters (17 out of 25) showed a clear directional selectivity. Oscillatory responses occurred in both directionally selective and nonselective cells.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…The average of the oscillation frequency was 52 Hz (SD = ±12 Hz; n = 19) and thus in the same range as that of responses in area 17 (11)(12)(13). In agreement with previous reports (18)(19)(20), most of the cell clusters (17 out of 25) showed a clear directional selectivity. Oscillatory responses occurred in both directionally selective and nonselective cells.…”
Section: Resultssupporting
confidence: 90%
“…This enabled us to verify the location of the electrode array in area PMLS by two additional criteria: (i) The spatial arrangement of the receptive fields agreed with the characteristic retinotopy of area PMLS; i.e., during electrode penetrations at the AP level chosen, the receptive fields moved toward the center of the visual field along the horizontal meridian (16). (ii) The receptive field properties of the cells encountered were characteristic of area PMLS; i.e., the cells had large directionally selective receptive fields, exhibited pronounced binocularity, and showed broad velocity tuning but poor orientation selectivity (18)(19)(20) Our methods for data processing have been described in detail (13). Auto-and cross-correlation functions were computed for all spike trains.…”
Section: Methodssupporting
confidence: 63%
See 1 more Smart Citation
“…Collectively, the present results and their implications indicate that subthreshold auditory influences observed in visual PLLS neurons are sensory in nature and undoubtedly contribute to the role of the retinotopically-organized region (Palmer et al, 1978) in visual motion processing (Rauschecker et al, 1987). These observations are also consistent with the receptive field-based sensory processing that occurs in bimodal multisensory neurons.…”
Section: Sensory Specific Cortical Activationsupporting
confidence: 84%
“…These results suggest that projections to FEF from posterior visual areas preserve the radial motion bias seen in MT and posterior parietal cortex~Steinmetz et al, 1987;Albright, 1989!, and that this bias is incorporated into motor commands for saccades. A radial motion bias has also been reported for cells in the lateral suprasylvian cortex of cats~LS; Rauschecker et al, 1987!, and recent studies have found evidence for an explicit representation of optic flow in cat LS~Li et al, 2000;Sherk & Fowler, 2001!. The preferred orientation of neurons in V1 also shows a radial bias~Bauer & Dow, 1989;Bauer et al, 1983;Leventhal, 1983;Vidyasagar & Henry, 1990!, suggesting that this form of representational bias may be ubiquitous in visual cortex.…”
Section: Discussionmentioning
confidence: 73%